Emergency Department Arrival Times, Treatment, and Functional Recovery in Women with Acute Ischemic Stroke - Knauft, Wesley (Mary Ann Liebert, Inc., 2010)
BACKGROUND: Sex disparities have been well documented in patients with ischemic stroke. Previous studies have suggested that female sex is a risk factor for delay in arrival time to the emergency department (ED) and may contribute to ineligibility for thrombolytic therapy. With the increase in education efforts targeting women, we investigated whether ED arrival times, rates of thrombolytic use, and functional outcomes continue to differ in men and women with acute ischemic stroke (AIS). METHODS: This study was a retrospective database analysis of patients with AIS (2001–2008). All AIS patients presenting within 24 hours with a known time of symptom onset and a documented admission National Institutes of Health Stroke Scale (NIHSS) were included. The Modified Barthel Index (MBI) assessed patients' functional status preadmission (historical), admission, and at 3 and 12 months poststroke. RESULTS: Included in the analysis were 480 (50.6%) women and 468 (49.4%) men. Women were significantly older than men (70.6 ± 0.7 vs. 65.3 years ± 0.6, p ≤ 0.001). Mean onset-to-ED time was not significantly different between the sexes (women 265 ± 283 vs. men 245 ± 300 minutes), nor was prestroke MBI. Logistic regression analysis demonstrated that female sex, increasing age, higher admission NIHSS, and longer onset-to-ED times all contributed to poorer functional status. CONCLUSIONS: Women arrive at the ED at equivalent speed as men after AIS. Women had greater functional impairments at 3 months and 12 months poststroke despite equivalent prestroke MBI and admission NIHSS. Female sex contributes to poorer chronic functional outcomes after AIS.